(untitled) (The Journal of Theoretical Accounting Research, 2025)
Municipal corporations constitute the third tier of government and increasing urbanisation has led to a massive demand for urban infrastructure which in turn underlines the need for adequate revenue provisioning. The paper has focused on the revenue performance employing two ratios viz ratio of own revenues to revenue receipts and, own revenues to revenue expenditure which reflect the revenue raising ability, fiscal autonomy and ability to support current expenditure for the time period 2019-20 to 202-23. The results indicate that on an average municipal corporations are able to raise and finance only 53-54 percent of their revenue requirements and hence there is a significant reliance on funds from the State and central government. The results of clustering analysis reiterates the findings on spatial effects.